纳米材料在肿瘤光热治疗中存在的问题及解决策略 = Problems and solutions of nanomaterials in antitumor photothermal therapy - Chang, Mengyu (2024)
由于其非侵入性、时空可控性和高效性，光热治疗（PTT）在抗肿瘤治疗领域迅猛发展。然而，PTT存在的一些问题阻碍了其进一步的临床转化。鉴于此，本文首先简要介绍了光热转换原理和PTT抗肿瘤机制。随后着重总结了PTT在发展过程中遇到的问题和不足，并列举了相应的解决策略，主要包括：调控纳米材料的形貌、构建异质结结构、选择合适的光学窗口来提高纳米材料的光热转换效率；设计多模态协同治疗模式来克服单一PTT的局限性；提高纳米材料的肿瘤富集量来增强抗癌治疗效果；以及构建肿瘤微环境激活的光热转换试剂和设计低温PTT模式来提高纳米药物的生物安全性。最后，对PTT的未来前景和发展进行了展望。Photothermal therapy（PTT） is developing rapidly in the field of antitumor therapy， due to its non-invasiveness， spatiotemporal controllability， and high efficiency. However， there are some practical problems in PTT， which hinder its further transition from basic scientific research to clinical applications. Herein， at first， this review briefly introduces the photothermal conversion principle and antitumor mechanism of PTT. Then， the main problems in the development of PTT are summarized， and those corresponding solutions are listed， including： enhancing the photothermal conversion efficiency by the control of nanomaterial morphology， the construction of heterojunction structures， and the adjustment of optical windows； overcoming the limitation of single PTT by the invention of collaborative treatment models； consolidating antitumor therapy effect by increasing tumor enrichment of nanomaterials； improving the biological safety of nanomedicine by the design of tumor microenvironment-activated photothermal complex and the realization of mild PTT. Finally， the future prospect and development of PTT are stated.